Changing regimes of gangotri and surrounding glaciers: A case study of Garhwal Himalaya, India - Rai P.K.; Mohan K.; Mishra V.N.; Biswari M.; Sharma A.; Rai S. (My University, 2025)
In the present study, 16 selected glaciers including Gangotri and surrounding covering an area of 2982.14 sq km, Garhwal Himalaya (Uttrakhand) India were mapped and their boundaries were delineated using the Landsat MSS (3rd November, 1976), TM (16th October, 1990), ETM+(18th October, 1999 and) and OLI-TIRS (29th Oct., 2013)) and ASTER images. In this study a total of 101 glacial lakes are identified in 2013 while the number of identified glacial lakes was 69 and 128 in 1990 and 1999. The valley of Gangotri glacier and Satopanth glacier show huge increase in number and area of glacial lakes especially supraglacial lakes. Several morphometric parameters like length, width, total area, perimeter, accumulation area, ablation area, area accumulation ratio (AAR), thickness etc. were estimated for detailed morphometric analysis among the mapped glaciers. The mapping of selected 16 glaciers during the period 1972-2013 reveals that the glacier covered area reduced from 409.08 to 377.83 sq km observing approx. 7.63% deglaciation in the Gangotri and surrounding area. Gangotri glacier shown a net loss of 4.68% area during 1972-2013 while it shows a net gain of 1.32% area during 1999-2013. Advancement in the total glacier area was also recorded during 1979-1999. A higher rate of retreat of the some of the glaciers was observed during 1989-2006 as compared to the retreat during 1972-1989. The average elevation of the ablation zone of Gangotri glacier showed an upward shift from 3944 m (1972) to 4033 m (2013) which may be a consequence of a shift in Equilibrium Line Altitude (ELA) reflecting imbalance. In this study it is estimated that the Gangotri glacier was retreated 1.60 km between 1972-2013. During the period of 1972-2013, it was observed that maximum retreat among selected 16 glacier were mainly Arwa, Raktavaran, Panpatia, Chaturangi, Satopant glaciers (9.47 km, 6.43 km, 3.87 and 3.04 km respectively). © 2016 Elsevier B.V.